Divorce, living arrangements, and material well-being during the transition to adulthood in rural Malawi - Grant, Monica J. (Popul Stud (Camb), 2019)
In this paper, we use longitudinal data to investigate how parental death and divorce influence young women’s own experience of divorce in Malawi, a setting where women marry relatively early and unions are fragile. We find that maternal death and parental divorce are positively associated with divorce for young women but, after controlling for socio-demographic and marital characteristics, only the association with maternal death remains statistically significant. Maternal and paternal death are both strongly associated with women’s post-divorce living arrangements, which in turn affects their material well-being. This finding suggests that divorcing at a young age shapes the subsequent life chances of women; although some women return to their parental home and may have the opportunity to reset the transition to adulthood, other women begin their twenties as head of their own household and with considerable material disadvantage.